2002
DOI: 10.1002/cbf.977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cod liver oil on tissue antioxidant pathways in normal and streptozotocin‐diabetic rats

Abstract: Lipid disorders and increased oxidative stress may exacerbate some complications of diabetes mellitus. Previous studies have implicated the beneficial effects of some antioxidants, omega-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the protection of cells from the destructive effect of increased lipids and lipid peroxidation products. This study, therefore, was designed to investigate the effects of cod liver oil (CLO, Lysi Ltd. Island), which comprises m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 34 publications
6
57
0
Order By: Relevance
“…All these effects were blocked by cod liver oil. Of note, it has been reported previously that cod liver oil reduced oxidative stress and augmented the antioxidant activity in other animal models that involve oxidative stress like streptozotocininduced diabetes in rats (Hunkar et al, 2002) and daunomycin-induced nephropathy in mice (Ohtake et al, 2002). Moreover, dietary supplementation with cod liver oil inactivates circulating neutrophils and plasma lipoperoxides (Guarnieri et al, 1991).…”
Section: Discussionmentioning
confidence: 90%
“…All these effects were blocked by cod liver oil. Of note, it has been reported previously that cod liver oil reduced oxidative stress and augmented the antioxidant activity in other animal models that involve oxidative stress like streptozotocininduced diabetes in rats (Hunkar et al, 2002) and daunomycin-induced nephropathy in mice (Ohtake et al, 2002). Moreover, dietary supplementation with cod liver oil inactivates circulating neutrophils and plasma lipoperoxides (Guarnieri et al, 1991).…”
Section: Discussionmentioning
confidence: 90%
“…However, several reports have shown the beneficial effects of fish oils containing n-3 polyunsaturated fatty acids (PUFAs) like eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the protection against lipid peroxidation in rat and human beings with diabetes. 15,16 Owing to these beneficial effects of n-3 PUFA, we tested the hypothesis whether EPA and DHA are implicated in prevention and protection against free radical production or oxidative stress associated with lipid peroxidation in diabetes. To our knowledge, no studies have directly investigated the role of EPA and DHA in lipid metabolism and oxidative stress in macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…The level of MDA, an end-product of LPO, signifi cantly increased in the liver of the untreated diabetic rats. Thus, increased MDA level in diabetes mellitus suggests that hyperglycaemia induces peroxidative reactions in lipids (42). Besides, it has been reported that diabetes increased oxidative stress in many organs, especially in the liver (29).…”
Section: Discussionmentioning
confidence: 95%